Correction: Synthesis and characterization of a strong ferromagnetic and high hardness intermetallic compound Fe2B. Issue 43 (28th October 2021) - Zhao, Xingbin; Li, Li; Bao, Kuo; Zhu, Pinwen; Tao, Qiang; Ma, Shuailing; Liu, Bo; Ge, Yufei; Li, Da; Cui, Tian
Abstract : Correction for 'Synthesis and characterization of a strong ferromagnetic and high hardness intermetallic compound Fe2 B' by Xingbin Zhao et al., Phys. Chem. Chem. Phys., 2020, 22, 27425–27432, DOI: ; 10.1039/D0CP03380D .